UPAYA PERCEPATAN PENCEGAHAN STUNTING MELALUI PEMANFAATAAN BAHAN PANGAN LOKAL PADA MENU MPASI DAN PEMAHAMAN PEDOMAN BUKU KIA DI KELURAHAN KANDANG MAS - Rismayani; Putri, Poppy Siska; Maulani, Nurul; Lety Arlenti (Fakultas Pertanian, 2024)
Stunting is a global issue, particularly in developing countries. One of the ways to prevent stunting is by providing age-appropriate complementary feeding (MP-ASI), while also avoiding the consumption of fast food and ultra-processed foods. In Kandang Mas Subdistrict, some young children are still experiencing weight faltering. This community service programme aims to help mothers and posyandu (integrated health post) cadres improve their knowledge about children's nutritional status through education and demonstrations on how to prepare MP-ASI using local ingredients. The programme was conducted in September 2024, involving 30 mothers of infants and toddlers, as well as 4 posyandu cadres. The methods used included education sessions, demonstrations, mentoring, and evaluation. The programme successfully enhanced the knowledge and skills of the mothers in preparing MP-ASI, and helped them to better understand the early signs and prevention of stunting. Participants (mothers of infants/toddlers and posyandu cadres) also gained a better understanding of children's nutritional status and the process of making MP-ASI using local food. The increase in knowledge was measured using the SPSS Wilcoxon test with a p-value of 0.03. The implementation of health education through education sessions, demonstrations, mentoring, and evaluation proved effective in improving knowledge. It is hoped that the mothers and posyandu cadres will apply the knowledge and skills gained to help reduce stunting rates in their area.